Effect on Microbial Growth of a New Skin Protectant Formulation - Stoffel, Joseph (Adv Wound Care (New Rochelle), 2017)
Objective: Evaluate the effect of a new investigational skin protectant formulation on the growth of various microorganisms in vitro. Approach: An in vitro laboratory assay with various species of gram-positive bacteria, gram-negative bacteria, and yeast grown on agar plates was used to verify that a new investigational product used for the management of incontinence-associated dermatitis (IAD) does not support microbial growth. Results: The investigational product did not support the growth of all organisms tested for 48 h in these assays. The results demonstrate the barrier properties of this investigational formulation against bacteria and yeast that are relevant to incontinent patients. Innovation: IAD accompanied by skin damage is difficult to manage with currently available products. A new skin protectant that can be applied as a liquid and polymerizes into a breathable film in situ even in the presence of exudate (as shown previously) has been developed and tested to ensure that it does not support microbial growth. Conclusion: This work verifies that this new product does not support microbial growth in vitro using organisms relevant for the intended application.